The Concept of E-Voting Mechanism Based on Law of General Election and Information Security - Bayu Sujadmiko; Iskardo P Panggar; Ade Sofyansah; Intan Fitri Meutia (Faculty of Law, Jambi University, 2020)
The development of technology has made transformation in the world; one of them is the implementation of e-voting systems in general elections. This research aims to dig deeper into the utilization of e voting in Indonesia's general election according to the Law on General Election, and research on the e-voting safety aspect in Indonesia's general election with the Law on ITE, government regulation on One Data Indonesia, and the Bill of Personal Data Protection Law. The research method is normative, which is delivered with an analytic-descriptive method. The results show that Indonesia has arranged elections with e-voting mechanisms for multiples of times, for example, in Jembrana Regency. Based on the General Election Law, e voting could be implemented in Indonesia. However, there are still considerations in terms of technology and preparation that should prevent unwanted burden. There needs to be a regulation for voters' data management to prevent violations against human rights. Data management must pay attention to safety aspects guided by the Law on ITE, government regulation on One Data Indonesia, and the Bill of Personal Data Protection Law